Tisagenlecleucel therapy for relapsed or refractory B-cell acute lymphoblastic leukaemia in infants and children younger than 3 years of age at screening: an international, multicentre, retrospective cohort study. Issue 10 (October 2022) - Ghorashian, Sara; Jacoby, Elad; De Moerloose, Barbara; Rives, Susana; Bonney, Denise; Shenton, Geoff; Bader, Peter; Bodmer, Nicole; Quintana, Agueda Molinos; Herrero, Blanca; Algeri, Mattia; Locatelli, Franco; et al.
Summary: Background: Children aged younger than 3 years were excluded from the ELIANA phase 2 trial of tisagenlecleucel in children with acute lymphoblastic leukaemia. The feasibility, safety, and activity of tisagenlecleucel have not been defined in this group, the majority of whom have high-risk ( KMT2A -rearranged) infant acute lymphoblastic leukaemia and historically poor outcomes despite intensification of chemotherapy, and for whom novel therapies are urgently needed. We aimed to provide real-world outcome analysis of the feasibility, activity, and safety of tisagenlecleucel in younger children and infants with acute lymphoblastic leukaemia. Methods: We did an international, multicentre, retrospective cohort study at 15 hospitals across ten countries in Europe. Eligible patients were children aged younger than 3 years at screening between Sept 1, 2018, and Sept 1, 2021, who were screened for tisagenlecleucel therapy for relapsed or refractory B-cell precursor acute lymphoblastic leukaemia according to licensed indications. Patients received a single intravenous infusion of tisagenlecleucel. We tracked chimeric antigen receptor T-cell therapy outcomes using a standardised data reporting form. Overall survival, event-free survival, stringent event-free survival, B-cell aplasia, and toxicity were assessed in all patients who received a tisagenlecleucel infusion. Findings: 38 eligible patients were screened, of whom 35 (92%) received a tisagenlecleucel infusion. 29 (76%) of 38 patients had KMT2A -rearranged acute lymphoblastic leukaemia, and 25 (66%) had relapsed after previous allogeneic haematopoietic stem-cell transplantation (HSCT). Patients had previously received a median of 2 lines (IQR 2–3) of (non-HSCT) therapy. Seven (18%) of 38 patients had received inotuzumab and 14 (37%) had received blinatumomab. After a median of 14 months (IQR 9–21) of follow-up, overall survival at 12 months after tisagenlecleucel infusion was 84% (64–93; five patients had died), event-free survival was 69% (47–83; nine events), and stringent event-free survival was 41% (23–58; 18 events). The probability of ongoing B-cell aplasia was 70% (95% CI 46–84; seven events) at 12 months. Adverse events included cytokine release syndrome, which occurred at any grade in 21 (60%) of 35 patients and at grade 3 or worse in five (14%), and neurotoxicity at any grade in nine (26%), none of which were severe. Measurable residual disease-negative complete response with or without haematological recovery occurred in 24 (86%) of 28 patients who had measurable disease. Interpretation: These data suggest that tisagenlecleucel has antitumour activity and has an acceptable safety profile for young children and infants with B-cell precursor acute lymphoblastic leukaemia. Funding: None.